2019
DOI: 10.18203/2320-1770.ijrcog20194608
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study on the efficacy of Pipelle biopsy to diagnose endometrial pathology in patients with abnormal uterine bleeding

Abstract: Background: Abnormal uterine bleeding is one of the most common problem encountered in gynaecology clinics. Assessment of endometrial pathology is recommended to rule out malignancy and premalignant conditions. Endometrial sampling can be done by Pipelle biopsy in outpatient units as well as by conventional dilatation and curettage in an operation theatre setup. Our study aims to find out the efficacy of office endometrial biopsy in terms of its sample adequacy, diagnostic accuracy and patient acceptability.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 10 publications
7
4
0
Order By: Relevance
“…This is also supported by a similar study done by Muzaffar et al 18 The incidence of the non-neoplastic lesion in our study was 91% and 4% were neoplastic lesions. This is similar to studies conducted by Mathew et al 16 , and Abdelazim IA et al 20 , and Chaudhary A et al 19 where sample adequacy was 96%, 97.9%, and 95% respectively and in our study, the sample adequacy was 95%. There were 05 cases of inadequate samples which is in comparison to a study conducted by Fakhar S et al 9 , where there were 02 inadequate samples and a similar study by Mathew et al 16 had 05 inadequate samples.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…This is also supported by a similar study done by Muzaffar et al 18 The incidence of the non-neoplastic lesion in our study was 91% and 4% were neoplastic lesions. This is similar to studies conducted by Mathew et al 16 , and Abdelazim IA et al 20 , and Chaudhary A et al 19 where sample adequacy was 96%, 97.9%, and 95% respectively and in our study, the sample adequacy was 95%. There were 05 cases of inadequate samples which is in comparison to a study conducted by Fakhar S et al 9 , where there were 02 inadequate samples and a similar study by Mathew et al 16 had 05 inadequate samples.…”
Section: Resultssupporting
confidence: 93%
“…Our study showed 78% sensitivity, 89% specificity for endometrial hyperplasia with atypia with 50% positive, and 97% negative predictive value. This is similar to a study by Mathew et al 16 and Sanam M et al 22 05 inadequate samples in our study were in the post-menopausal age group, they went on to have diagnostic dilation and curettage which showed atrophic endometrium on histopathology. This is comparable to a study done by Asif et al 21 where inadequate samples were 04%.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In the study by Zutshi et al .,[ 10 ] no significant difference in pain score was observed in Karman cannula and Endosampler groups, with both showing less pain. Mathew and Thomas[ 29 ] observed that most of the patients required no analgesics after Karman cannula use. Thus, it can be said that Karman cannula and Pipelle use is associated with less pain, however, between both of them, we advocate Karman cannula in terms of pain threshold.…”
Section: Discussionmentioning
confidence: 99%